PERBANDINGAN UJI KEBOCORAN TEPI RESIN KOMPOSIT FLOWABLE DAN BAHAN LUTING SEMEN PADA PASAK POLYETHYLENE FIBER-REINFORCED (PFR) - Malun Nasrudin; Dwi Warna Aju Fatmawati; FX Ady Soesetijo (Odonto : Dental Journal, 2016)
Background: Zinc phosphate, glass-ionomer, and resin cement are the most commonly used as luting cements. Flowable composite resin could reduce restoration microleakage and provided better marginal seal in dentin. Purpose: The objective of the study was to compare microleakage between flowable composite resin and cement luting materials.Methods: The study was experimental laboratory by the post test only without control group design. The sample size was 18, which was divided into 3 groups. Each group consisted of 6 samples. Glass-ionomer cement and zinc phosphate were luting cement materials that used in the study. Microleakage measurement method used stereomicroscope after the samples were stored in methylen blue 0.25%.Results: The smallest average value of microleakage was in the flowable composite resin group (29,16%). One way ANOVA test results showed that there were significant differences between treatment groups (p=0.000). Conclusion: It was concluded that flowable composite resin have smaller microleakage average value than glass-ionomer cement and zinc phosphate.